2016
DOI: 10.1111/eci.12642
|View full text |Cite
|
Sign up to set email alerts
|

Increased thioredoxin levels are related to insulin resistance in familial combined hyperlipidaemia

Abstract: Familial combined hyperlipidaemia patients showed increased TRX levels. TRX was positively correlated with IR. These data could partially explain the increased risk of cardiovascular events in primary dyslipidemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This could be partly explained by the chronic proinflammatory state and increased oxidative stress that has been observed in FCH subjects, particularly those with insulin resistance. 4 9 10 In the present study, we have observed that, compared with controls, FCH subjects have increased MPO and PAI-1 blood values. The elevation of these two proinflammatory and proatherothrombotic biomarkers was significantly higher in the presence of insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…This could be partly explained by the chronic proinflammatory state and increased oxidative stress that has been observed in FCH subjects, particularly those with insulin resistance. 4 9 10 In the present study, we have observed that, compared with controls, FCH subjects have increased MPO and PAI-1 blood values. The elevation of these two proinflammatory and proatherothrombotic biomarkers was significantly higher in the presence of insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…In FCHL, there is an upregulation of thioredoxins, which are disulfide reductases responsible for regulating redox reactions, and confers an increased oxidative stress with reduced glutathione levels associated to IR. Both the increase in oxidative stress damage and IR contribute to atherosclerosis and potentially to increased cardiovascular risk in FCHL patients 38 . Most FCHL patients have increased sdLDL and apoB levels for all levels of IR in comparison to controls, adjusted by HOMA-IR and BMI 9 ; this supports the concept that the etiology of the lipid phenotype in FCHL is a result of additive effects of genetic determinants with modulation by BMI and IR.…”
Section: Pathophysiology Of Fchlmentioning
confidence: 99%
“…
The 2017 ESCI Award for the Best Clinical Research Article goes to the study by Christopher Adlbrecht and co-workers, entitled 'Outcome of conservative management vs. assist device implantation in patients with advanced refractory heart failure' [1]. This article was selected among seven finalist articles of outstanding quality and scientific impact [2][3][4][5][6][7].Although cardiac transplantation is recommended in terms of lasting clinical outcomes in patients with advanced refractory heart failure (HF) [8], the lack of organ donors and the ineligibility of some patients imply the need for improving alternative medical and surgical therapeutic strategies.In this retrospective study, the authors assessed clinical outcomes at 24-month follow-up of conservatively vs. surgically treated patients with refractory heart failure (HF) at the Medical University of Vienna. Of the 118 patients enrolled, 50 (42%) were conservatively managed using optimized medical therapy (OMT), while 69 (58%) were treated with the implantation of a ventricular assist device (VAD).
…”
mentioning
confidence: 99%
“…The 2017 ESCI Award for the Best Clinical Research Article goes to the study by Christopher Adlbrecht and co-workers, entitled 'Outcome of conservative management vs. assist device implantation in patients with advanced refractory heart failure' [1]. This article was selected among seven finalist articles of outstanding quality and scientific impact [2][3][4][5][6][7].…”
mentioning
confidence: 99%